2020
DOI: 10.1021/acsami.0c01622
|View full text |Cite
|
Sign up to set email alerts
|

Capsules of Reactive Ionic Liquids for Selective Capture of Carbon Dioxide at Low Concentrations

Abstract: The task-specific ionic liquid (IL), 1-ethyl-3-methylimidazolium 2-cyanopyrolide ([EMIM]­[2-CNpyr]), was encapsulated with polyurea (PU) and graphene oxide (GO) sheets via a one-pot Pickering emulsion, and these capsules were used to scrub CO2 (0–5000 ppm) from moist air. Up to 60 wt % of IL was achieved in the synthesized capsules, and we demonstrated comparable gravimetric CO2 capacities to zeolites and enhanced absorption rates compared to those of bulk IL due to the increased gas/liquid surface-to-volume a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 65 publications
4
71
0
Order By: Relevance
“…It has been reported that the gravimetric capacity and viscosity can be further improved by the choice of the cation. , We have previously shown that the challenge of CO 2 transport in viscous rILs can be mitigated by encapsulation, where the gas–liquid surface area is enhanced dramatically for improved mass transport . More recently, we have reported CO 2 capacities of 1.5 mol CO 2 per kg of sorbent for capsules of 1-ethyl-3-methylimidazolium 2-cyanopyrrolide, [EMIM]­[2-CNpyr] (60 wt % of capsule), at 25 °C and low partial pressures of CO 2 (<0.1 bar) . Regeneration was achieved at 40 °C with no loss of capacity upon repeated absorption–desorption cycles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the gravimetric capacity and viscosity can be further improved by the choice of the cation. , We have previously shown that the challenge of CO 2 transport in viscous rILs can be mitigated by encapsulation, where the gas–liquid surface area is enhanced dramatically for improved mass transport . More recently, we have reported CO 2 capacities of 1.5 mol CO 2 per kg of sorbent for capsules of 1-ethyl-3-methylimidazolium 2-cyanopyrrolide, [EMIM]­[2-CNpyr] (60 wt % of capsule), at 25 °C and low partial pressures of CO 2 (<0.1 bar) . Regeneration was achieved at 40 °C with no loss of capacity upon repeated absorption–desorption cycles.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing these properties, perfect IL can be chosen for the particular application. ILs can be utilized in a variety of fields such as synthesis of organic and inorganic materials, electrochemistry, catalysis as well as bio-catalysis reactions, materials science, and separation technology (Chotkowski et al, 2020 ; Gholami et al, 2020 ; Lee et al, 2020 ; Nasirpour et al, 2020 ; Su et al, 2020 ; Yin et al, 2020 ). Imidazolium-based ILs have become the focus of much research because of the presence of the imidazole ring in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other applications of SAILs can be listed as foaming and antifoaming agents, antimicrobials, demulsification of crude oil, chromatographic and electrophoretic separations, enhanced oil recovery (EOR), solubilization of drugs, extraction of natural products etc. (Shah et al, 2018a , 2020 ; Vaid et al, 2018a , b ; Dani et al, 2019 ; Isosaari et al, 2019 ; Kuddushi et al, 2019 , 2020 ; Shakeel et al, 2019 ; Lee et al, 2020 ; Nandwani et al, 2020 ; El Seoud et al, 2021 ). SAILs can be of different kinds based upon their structure.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the use of a task-specific IL can be used to further enhance CO 2 uptake and release performance (i.e., use of an IL that reversibly reacts with CO 2 ). 45 Thus, capsules of different ILs with shells of polyurea and nanosheets have various applications, including CO 2 capture, but the impact of the identity of the polymer component of the shell on CO 2 capacity and absorption rate is unclear.…”
Section: Introductionmentioning
confidence: 99%